(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence in Italy of the following species of Homoptera Coccoidea is reported. The species are: Antoninella inaudita Kiritchenko, Mirococcopsis nagyi Kozar, Rhizoecus poltavae Laing, Trionymus hamberdi (Borchsenius) (Fam. Pseudococcidae); Eriococcus micracanthus (Danzig), Rhizococcus agropyri Borchsenius (Fam. Eriococcidae), Eulecanium douglasi (Sule) (Fam. Coccidae). Moreover the incidental introduction in Italy of two exotic species, namely Umbaspis regularis (Newstead) (Fam. Diaspididae) and Protopulvinaria pyriformis (Cockerell) (Fam. Coccidae), is pointed out. The former is an African species, recognized in Italy on a palm, the latter, largely distributed in the subtropical region and considered an occasional pest of Citrus, tropical fruit trees and ornamentals, was collected in Italy on an ornamental undetermined shrub.